Human liver apolipoprotein B-100 cDNA: complete nucleic acid and derived amino acid sequence. - Law, S W (1986)
Human apolipoprotein B-100 (apoB-100), the ligand on low density lipoproteins that interacts with the low density lipoprotein receptor and initiates receptor-mediated endocytosis and low density lipoprotein catabolism, has been cloned, and the complete nucleic acid and derived amino acid sequences have been determined. ApoB-100 cDNAs were isolated from normal human liver cDNA libraries utilizing immunoscreening as well as filter hybridization with radiolabeled apoB-100 oligodeoxynucleotides. The apoB-100 mRNA is 14.1 kilobases long encoding a mature apoB-100 protein of 4536 amino acids with a calculated amino acid molecular weight of 512,723. ApoB-100 contains 20 potential glycosylation sites, and 12 of a total of 25 cysteine residues are located in the amino-terminal region of the apolipoprotein providing a potential globular structure of the amino terminus of the protein. ApoB-100 contains relatively few regions of amphipathic helices, but compared to other human apolipoproteins it is enriched in beta-structure. The delineation of the entire human apoB-100 sequence will now permit a detailed analysis of the conformation of the protein, the low density lipoprotein receptor binding domain(s), and the structural relationship between apoB-100 and apoB-48 and will provide the basis for the study of genetic defects in apoB-100 in patients with dyslipoproteinemias.